Pemahaman Akuntansi dan Pemanfaatan Teknologi Informasi dalam Peningkatan Kualitas Laporan Keuangan - Nugraha, Hari Satia; Maria Ulfha, Sri; Asyifa, Nita Laila; Lasamanah, Lasamanah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of accounting understanding and utilization of information technology on improving the quality of financial reports. The research method used is quantitative with a survey approach by distributing questionnaires to respondents involved in the preparation of financial reports. The population in the study amounted to 168 people who work in the finance department of companies located in West Bandung, West Java, sampling using the Slovin formula with an error rate of 5% so that the sample amounted to 119 respondents. The results of the study indicate that both accounting understanding and utilization of information technology have a positive and significant effect on the quality of financial reports. Good quality financial reports are very important in supporting the right decision making for stakeholders. Adequate accounting understanding allows the preparation of reports in accordance with applicable accounting principles, while information technology plays a role in accelerating the process of recording, processing, and presenting financial data accurately and on time. Thus, improving accounting competence and utilizing adequate information systems is highly recommended to improve the transparency and accountability of the company's financial reports.